Music and Public Health A Nordic Perspective (Springer International Publishing, 2018)
From the Nordic countries (Denmark, Norway, Sweden and Finland) comes an exciting source of theoretical approaches, epidemiological findings, and real-life examples regarding the therapeutic and health-enhancing effects of music. Experts across fields including psychology, neurology, music therapy, medicine, and public health review research on the benefits of music in relieving physiological, psychological, and socioemotional dysfunction. Chapters link musical experiences (listening and performing, as well as involvement in movement, dance, and theatre) to a wide range of clinical and non-clinical objectives such as preventing isolation, regulating mood, reducing stress and its symptoms, and treating dementia. And the book's section on innovative music-based interventions illustrates opportunities for incorporating musical activities into public health programs. Among the topics covered are: · Associations between the use of music, cultural participation and health-related outcomes in adult Scandinavian populations · Music practice and emotion handling · How music translates itself biologically in the body · Music as a forum for social-emotional health · Participation and partnership as core concepts in music and public health · Music therapy as health promotion for mothers and children at a public health clinic Music and Public Health will gain interested readers among researchers, teachers, students, and clinicians in the fields of music education and therapy, as well as researchers and students of public health who are interested in the influence of culture and the arts. The book also will be relevant to administrators in public health services.